Demand-driven vegetable breeding for impact - Barchenger, Derek; Zohoungbogbo, Herbaud; Ambali, Mwasilwa; Nalla, Manoj Kumar; Eybishitz, Assaf; Schreinemachers, Pepijn (CGIAR, 2025)
The success of vegetable breeding programs depends not only on yield but also on the development of cultivars that align with the needs and preferences of actors across the value chain. Pest and disease resistance as well as key quality traits are critically important for ensuring the adoption of new varieties, particularly by smallholder farmers. To achieve this, vegetable breeding must be demand-driven, incorporating comprehensive feedback from users throughout the value chain. At the World Vegetable Center (WorldVeg), breeding efforts begin with strong partnerships with the private seed sector, which shares common objectives for varietal improvement. This collaboration is further validated through a systematic approach that includes experimental diagnostics of pest and disease resistance, field visits to assess performance under real farming conditions, and stakeholder engagement with farmers, nursery owners, traders, exporters, and processors. Participatory cultivar selection, particularly at the final stage before variety registration and release, is a critical component of this approach. A feedback mechanism ensures that breeding decisions are informed by end-user needs, ultimately enhancing the adoption of improved cultivars by smallholder farmers and contributing to sustainable agricultural development.